Hormonal Alterations in Women with Polycystic Ovarian Syndrome - Nafi Ahmed Saud; Eman Naji Saleh; Elham Ahmed Mejbel (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Polycystic ovary syndrome (PCOS) is among the most common endocrine disorders affecting 5–10% of women of reproductive age, associated with infertility, metabolic dysfunction, and cardiovascular risk. Specific background: Although PCOS is widely studied, the hormonal mechanisms underlying its heterogeneity remain insufficiently clarified, particularly in Middle Eastern populations. Knowledge gap: Limited data exist on the hormonal alterations across age groups of women with PCOS in Iraq, where prevalence is rising. Aims: This study investigated hormonal parameters—LH, FSH, testosterone, prolactin, T3, and TSH—among 50 PCOS patients compared with 25 healthy controls in Ramadi. Results: Findings showed significantly elevated LH, testosterone, prolactin, and TSH, alongside reduced T3, with the most pronounced LH increase in women aged 36–45 years (p < 0.05). FSH remained unchanged overall, while clinical signs such as menstrual irregularities, obesity, hirsutism, and galactorrhea were markedly more frequent in PCOS cases. Novelty: This study provides age-stratified evidence linking hormonal imbalances with clinical manifestations in Iraqi women, highlighting hypothyroidism as a contributing factor. Implications: The results underscore the importance of routine thyroid and hormonal monitoring, genetic screening, and lifestyle interventions in managing PCOS and reducing its reproductive and metabolic complications Highlights: PCOS patients showed significantly elevated LH, testosterone, prolactin, and TSH with reduced T3. Age group 36–45 years exhibited the highest hormonal imbalance, especially LH increase. Clinical manifestations included menstrual irregularities, obesity, hirsutism, and galactorrhea Keywords: Polycystic Ovary Syndrome, Hormonal Imbalance, Luteinizing Hormone, Hypothyroidism, Infertility